2017
DOI: 10.1515/iss-2017-0021
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of rectal foreign bodies: a 10-year single-center experience

Abstract: Background: Patients with a rectal foreign body (RFB) are still a rare entity in general surgery departments but with an increasing incidence over the last years. This case is sometimes difficult to treat, and due to a lack of standardized treatment options, the aim of the study was to present our clinical experiences with the diagnostic and therapeutic approach to RFBs and a review of the currently available literature. Materials and methods: Data were collected retrospectively from the patient's records of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 23 publications
0
23
0
4
Order By: Relevance
“…Eine zügige Entfernung in der Notaufnahme ohne Gabe einer Narkose war in dieser hier vorliegenden Serie nur bei 2 von 9 Patienten erfolgreich, obwohl der Fremdkörper im Rektum lokalisiert war. In der kürzlich publizierten deutschsprachigen Arbeit von Kokemohr et al lag die Erfolgsrate hingegen bei 70 % [4]. Auch wenn der Fremdkörper im Rektum lokalisiert und tastbar ist, kann sich die Entfernung durch die sakrale Kurvatur und den mit jeder erneuten Manipulation zunehmenden Sphinktertonus erschweren [21].…”
Section: Methodikunclassified
See 1 more Smart Citation
“…Eine zügige Entfernung in der Notaufnahme ohne Gabe einer Narkose war in dieser hier vorliegenden Serie nur bei 2 von 9 Patienten erfolgreich, obwohl der Fremdkörper im Rektum lokalisiert war. In der kürzlich publizierten deutschsprachigen Arbeit von Kokemohr et al lag die Erfolgsrate hingegen bei 70 % [4]. Auch wenn der Fremdkörper im Rektum lokalisiert und tastbar ist, kann sich die Entfernung durch die sakrale Kurvatur und den mit jeder erneuten Manipulation zunehmenden Sphinktertonus erschweren [21].…”
Section: Methodikunclassified
“…Fallberichte ziehen sich in der Literatur durch sämtliche Jahrzehnte [2]. Manche Autoren beschreiben gar eine steigende Inzidenz [3,4].…”
Section: Kolorektale Fremdkörpereine Herausforderung Für Patient Und unclassified
“…Diagnostic dilemmas often arises as patients are sometimes unwilling to disclose the actual history and seek medical attention late. 1,2 Ooi et al from a study of 35 patients reported that only 33% admit to transanal insertion, while 67% complained of anal pain at the point of presentation. 3 Other presentations are per-rectal bleeding, mucous discharge, there are reported cases of local injury or perforation in attempts to remove the object.…”
Section: Introductionmentioning
confidence: 99%
“…3 Other presentations are per-rectal bleeding, mucous discharge, there are reported cases of local injury or perforation in attempts to remove the object. 1 Various types of foreign body have been reported, from bottles to bones, toys, fruits, vegetables, drugs, pipe hose, egg ornament, sprays, cans and many more. 2,4 Majority of cases are inserted via anus for sexual adventures voluntarily and occasionally as result of assault or rape.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation